1983
DOI: 10.3750/aip1983.13.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Effect of physiological factors, stress, and disease on haematological parameters of carp, with a particular reference to leukocyte pattern. I. Variability of haematological indices of carp in relation to age and gonad maturity stage

Abstract: The paper concerns the hematological parameters of carp (Cyprinus carpio L.) as related to the age of fish and changes occurring during the spawning period. In blood samples the red and white cell counts, hematocrit, hemoglobin concen tration, MCV, MCH, and MCHC were determined, and the leukogram and morphology of blood cells were examined in detail. The results obtained were treated statistically.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
(29 reference statements)
0
6
0
Order By: Relevance
“…Nucleus is conipletcly covered with melanin granules. MGG economically important fish species such as rainbow trout (Lehmann and Stiirenberg 1976), carp (Sopinska 1983), pike (Mulcahy 1970) or eel (Klinger 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Nucleus is conipletcly covered with melanin granules. MGG economically important fish species such as rainbow trout (Lehmann and Stiirenberg 1976), carp (Sopinska 1983), pike (Mulcahy 1970) or eel (Klinger 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indeed shown that hemoglobin levels fluctuate dramatically seasonally and especially during the spawning period (Robertson et al 1961;Sopinska 1983) and that hemoglobin levels also demonstrate a marked gender difference with males tending to have higher hemoglobin levels than females (Robertson et al 1961;Sopinska 1983;Habekovic 1991). Since triploid females remain sexually immature, neglecting to control for sexual maturity in experimental diploids may have distorted results in previous studies; neglecting to control for gender in previous studies may have produced further distortions.…”
Section: Discussionmentioning
confidence: 99%
“…According to Sopińska (1983), RBC and hemoglobin concentration (Hb) were higher in older C. carpio compared to the fingerlings. Similarly, Svetina et al (2002) reported increased erythropoiesis in carp during an intensive growth period in the second year of life compared to the younger fish.…”
Section: Erythrocytesmentioning
confidence: 97%
“…In aquatic environment, O 2 availability may considerably vary, and fish react to hypoxic conditions with elevation of blood oxygen carrying capacity -a rapid release of stored cells from a splenic reservoir or an increase in erythropoietic rate (Houston, Roberts, and Kennington 1996). Ambient temperature is the most important factor affecting metabolic rate in poikilotherm animals, and it causes seasonal changes in fish red blood cell parameters: higher RBC is observed at higher temperatures (Sopińska 1983;Svetina et al 2002). In addition, other abiotic factors such as water pH or salinity affect erythrocyte count in fish.…”
Section: Erythrocytesmentioning
confidence: 99%